Diagnostic testing for interstitial lung disease in common variable immunodeficiency: a systematic review - Bintalib, Heba M.; van de Ven, Annick; Jacob, Joseph; Davidsen, Jesper Rømhild; Fevang, Børre; Hanitsch, Leif G.; Malphettes, Marion; van Montfrans, Joris; Maglione, Paul J.; Milito, Cinzia; Routes, John; Warnatz, Klaus; et al. (Frontiers in Immunology, 2023)
Introduction Common variable immunodeficiency related interstitial lung disease (CVID-ILD, also referred to as GLILD) is generally considered a manifestation of systemic immune dysregulation occurring in up to 20% of people with CVID. There is a lack of evidence-based guidelines for the diagnosis and management of CVID-ILD. Aim To systematically review use of diagnostic tests for assessing patients with CVID for possible ILD, and to evaluate their utility and risks. Methods EMBASE, MEDLINE, PubMed and Cochrane databases were searched. Papers reporting information on the diagnosis of ILD in patients with CVID were included. Results 58 studies were included. Radiology was the investigation modality most commonly used. HRCT was the most reported test, as abnormal radiology often first raised suspicion of CVID-ILD. Lung biopsy was used in 42 (72%) of studies, and surgical lung biopsy had more conclusive results compared to trans-bronchial biopsy (TBB). Analysis of broncho-alveolar lavage was reported in 24 (41%) studies, primarily to exclude infection. Pulmonary function tests, most commonly gas transfer, were widely used. However, results varied from normal to severely impaired, typically with a restrictive pattern and reduced gas transfer. Conclusion Consensus diagnostic criteria are urgently required to support accurate assessment and monitoring in CVID-ILD. ESID and the ERS e-GLILDnet CRC have initiated a diagnostic and management guideline through international collaboration. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022276337.